Real Options Theory and analysis on pharmaceutical R&D project valuation - Gao, Yuan (2007)
The most widely used appraisal approach is discounted cash flow, such as NPV analysis. However, the traditional appraisal approaches fails to capture management flexibility during the project evaluation process. A new appraisal approach solves this problem and provides value for inherent managerial flexibility in most R&D projects. In this dissertation, after a careful review of the literature, including the basic definition of real option, type of real option, financial options versus real option and option pricing models, the comparison of traditional valuation approach with the real option approach is conducted by using both theoretical and practical application on compound option. Although there are some critiques on the application of the option pricing model to real asset, the results of the application obtained by comparing with those obtained through the traditional NPV analysis suggest that real option appraisal approach can be used as an important tool to value management flexibility and help managers to think clearly and strategically in a decision making process.